MEMBANGUN KEPEMIMPINAN KRISTEN ENTREPRENEURIAL SEBAGAI LANDASAN KEBERHASILAN UPAYA MEMIMPIN (BUILDING ENTREPRENEURIAL CHRISTIAN LEADERSHIP AS A FUNDAMENTAL OF SUCCESSFUL LEADING EFFORTS) - Yusak Tanasyah; Iswahyudi Iswahyudi; Steven Phang (Widya Agape School of Theology and Indonesia Christian Theologians Association, 2020)
Why are some leaders successful, while others fail? The truth is that there is no